Excess short-term mortality in women after isolated coronary artery bypass graft surgery. Issue 1 (22nd March 2016) - Filardo, Giovanni; Hamman, Baron L; Pollock, Benjamin D; da Graca, Briget; Sass, Danielle M; Phan, Teresa K; Edgerton, James; Prince, Syma L; Ring, W Steves
Abstract : Objective: Female sex is considered a risk factor for adverse outcomes following isolated coronary artery bypass graft (CABG) surgery. We assessed the association between sex and short-term mortality following isolated CABG, and estimated the 'excess' deaths occurring in women. Methods: Short-term mortality was investigated in 13 327 consecutive isolated CABG patients in North Texas between January 2008 and December 2012. The association between sex and CABG short-term mortality, and the excess deaths among women were assessed via a propensity-adjusted (by Society of Thoracic Surgeons-recognised risk factors) generalised estimating equations model approach. Results: Short-term mortality was significantly higher in women than men (adjusted OR=1.39; 95% CI 1.04 to 1.86; p=0.027). This significantly greater risk translates into 35 'excess' deaths among women included in this study (>10% of the total 343 deaths in the study cohort) and into 392 'excess' deaths among the ∼40 000 women undergoing isolated CABG in the USA each year. Conclusions: The higher risk associated with female sex lead to 35 'excess' deaths in women in this study cohort (over 10% of the total deaths) and to 392 'excess' deaths among women undergoing isolated CABG in the USA each year. Further research is needed to assess the causal mechanisms underlying this sex-related difference. Results of such work could inform the development and implementation of sex-specific treatment and management strategies to reduce women's mortality following CABG. Based on our results, if such work brought women's short-term mortality into line with men's, total short-term mortality could be reduced by up to 10%.